Pendampingan dan Intervensi pada Anak Stunting di Rumah Belajar GKKD Buper Waena - Astrina Rosaria Indah; Yemima Christiani; Inneke Viviane Sumolang; Ferry Rhendra Pananda Putra Sitorus (Pakis Journal Institute, 2026)
Six children participated in the Rumah Belajar program at GKKD Buper Waena. They received direct stunting intervention for 6 months from August to January. Rumah Belajar partnered with Yayasan Obor Berkat Indonesia to provide supplementary food to 6 participating children. Previously, a meeting was held with a team of experts consisting of psychologists, doctors, and education practitioners. The psychologist conducted an intelligence assessment of the participants. The assistance was provided by 2 volunteers from the home learning tutors and one of the target participants. The medical staff conducts interviews with parents to determine the socio-economic factors that affect children's nutritional fulfilment and their daily eating patterns. The provision of animal protein-rich food is done every Monday, Tuesday, Wednesday, Thursday, and Sunday. The Tutor staff conducts height and weight checks every month as part of the evaluation. The Psychology Team conducted intelligence assessments on 6 participants who are experiencing stunting. The result obtained is that 3 people have below-average intelligence. The service team educated the parents of the participants about providing supplementary food. The provision of animal protein-rich food was carried out to intervene with 6 participants who are experiencing stunting. Community service was conducted from August 2025 to January 2026. Nutritional status evaluations are conducted by volunteers at the end of each month. The conclusion of the Community Service for the participants of the GKKD Buper Waena Learning House met the target, which is an increase in weight and height after 6 months of activities. The stunting assistance and intervention carried out successfully improved the nutritional status of the target participants.